Fish Parasitological Studies in Bangladesh: A Review - Chandra, KJ (Journal of Agriculture & Rural Development, 2008)
Fish parasitological investigation and research performed in Bangladesh has been reviewed through study of available literature. Considerable works mainly on systematics, nature of infestation and pathology of different groups of fish parasites- protozoa, helminths and crustacea have been done. A total of 290 species of parasites have so far been recorded from freshwater and marine fishes in Bangladesh. Ectoparasitic protozoans and monogenetic trematodes are recorded mainly from cultured fish species of farms. Two helminth parasites of zoonotic importance Dibothriocephalus latus and Gnathostoma spinigerum are also reported from Bangladesh fishes. Much attention has been given on caryophyllid cestodes of two catfishes Magur and Singhi. Few fish diseases of parasitic origin have been reported and studied. Commonly occurring parasitic diseases are agrulosis (fish louse), ichthyophthiriasis (white spot) and myxoboliasis. Only few attempts were taken to their control measures using simple chemicals like salt, lime, formalin, dipterex and sumithion. Recommendation has been made for the future works on parasitology for sustainable production of healthy fish. Key words: Fish parasites, freshwater fishes, marine fishes.